Fluctuation of simian virus 40 (SV40) super T-antigen expression in tumors induced by SV40-transformed mouse mammary epithelial cells. - Butel, J S (1986)
Higher-molecular-weight forms of the simian virus 40 (SV40) large tumor antigen (T-Ag), designated super T-Ag, are commonly found in SV40-transformed rodent cells. We examined the potential role of super T-Ag in neoplastic progression by using a series of clonal SV40-transformed mouse mammary epithelial cell lines. We confirmed an association between the presence of super T-Ag and cellular anchorage-independent growth in methylcellulose. However, tumorigenicity in nude mice did not correlate with the expression of super T-Ag. In the tumors that developed in nude mice, super T-Ag expression fluctuated almost randomly. Cell surface iodination showed that super T-Ag molecules were transported to the epithelial cell surface. The biological functions of super T-Ag remain obscure, but it is clear that it is not important for tumorigenicity by SV40-transformed mouse mammary epithelial cells. Super T-Ag may be most important as a marker of genomic rearrangements by the resident viral genes in transformed cells.